Postoperative pain management after sinus surgery: a survey of the American Rhinologic Society. Issue 10 (18th July 2018) - Gray, Mingyang L.; Fan, Caleb J.; Kappauf, Catharine; Kidwai, Sarah; Colley, Patrick; Iloreta, Alfred Marc; Govindaraj, Satish
Abstract : Background: Postoperative pain management is controversial as there are no current guidelines to direct clinical practice. The purpose of this study was to demonstrate prescribing patterns for pain management after functional endoscopic sinus surgery (FESS). Methods: A 15‐item web‐based survey was electronically distributed to 1770 members of the American Rhinologic Society (ARS). Linear regression analysis was used to determine associations between providers and prescribing patterns. Results: The survey was completed by 168 members (9.49%), representing all regions of the United States. The most commonly prescribed medications were opioid/non‐opioid combination pills. One hundred fifty‐seven of 168 members (94.05%) prescribed at least one kind of opioid after FESS, with an average of 27.38 pills. The majority of surveyed members worked in private or academic settings. Academic physicians were less likely to prescribe ibuprofen ( p = 0.0407), and nonsteroidal anti‐inflammatory drugs (NSAIDs) in general ( p = 0.032). Physicians in private practice were less likely to refer patients to pain management ( p = 0.0117), but more likely to refer patients to nontraditional forms of pain management ( p = 0.0164). Academic physicians were more likely to refer patients to pain management ( p = 0.00121). There was no association between perception of pain control and the prescription of NSAIDs or with number of opioid pills prescribed. Conclusion: Most providers prescribed opioids after FESS. There was no significant difference in the number of opioids prescribed based on geography or practice setting. There was significant heterogeneity in the adjuvant pain management strategy between academic and private practitioners. Most members provided patient education and few reported poor pain control. However, there was a gap in understanding of appropriate medication disposal and evidence‐based postoperative pain management.